Management techniques for the control of Melinis minutiflora P. Beauv. (molasses grass) : ten years of research on an invasive grass species in the Brazilian Cerrado - Martins, Carlos Romero (2017)
The invasion of exotic species is considered to be a major threat to the preservation of biodiversity. In the Parque Nacional de Brasília (National Park of Brasília), the invasive Melinis minutiflora (molasses grass) occupies more than 10 % of the area of the park. The present, long-term, study compared two treatments of exposure to molasses grass: 1) fire and 2) integrated management (fire + herbicide sprays + manual removal). The aerial biomass of molasses grass in the experimental area initially represented ca. 55 % of the total aerial biomass, a percentage that apparently did not influence native plant species richness at this site. Fire alone was not sufficient to control molasses grass, which attained its pre-treatment biomass values after two years. Integrated management reduced, and maintained, biomass to less than 1 % of its original value after ten years, and maintained this level throughout the study, demonstrating that it is a promising strategy for the recovery of areas invaded by molasses grass in the Cerrado. However, because of the recolonization by molasses grass, long-term monitoring efforts are targeting outbreaks, which would require immediate intervention in order to maintain the native biological diversity of the region.